Demographic features affecting on postpartum depression - Salehi, L; Tavafian, S; Salehi, F (Advances in Nursing & Midwifery, 2009)
Background Postpartum depression is a common disorder affecting on maternal-neonatal bonding. Purpose This analytical study was performed to identify demographic features influencing on postpartum depression in 2007. Methods 246 women having normal vaginal delivery with no history of physical and mental disorders during pregnancy or earlier were selected in a healthcare setting affiliated to Hormozgan Medical University. They were assessed on day 40 after delivery with 2 demographic and Edinburg’s questionnaires in terms of parity, educational level of spouses, neonatal disorders, sex of neonate, occupation of spouse, family planning, and decision for abortion, marital satisfaction, and history of stillborn babies. Results A significant difference was found between the groups in terms of marital relationships, level of education, sex of neonate, decision for abortion and unwanted pregnancy while there was no difference in parity, occupation of spouse and age. Conclusion It can be concluded that women having unwanted pregnancies with lower educational level, unsatisfactory relationship with their spouses and undesired sex of their babies should receive more help in preventive programs for postpartum depression. Keywords: Postpartum depression, Edinburg’s depression test, Demographic characteristics.